Neoplastic Hematopathology Experimental and Clinical Approaches - Jones, Dan.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2010)
Fulfilling the void with a Hematopathology book that integrates clinical and experimental studies with diagnostic criteria, Neoplastic Hematopathology: Experimental and Clinical Approaches provides an overview of the discipline of hematopathology that connects the field with recent advances in immunology research and current clinical practice in the treatment of lymphomas and leukemias. Designed for both trainees and specialists in pathology and hematology-oncology, Neoplastic Hematopathology: Experimental and Clinical Approaches has separate sections on laboratory techniques, diagnostic hematopathology, treatment and stem cell transplantation. Expert chapter authors address both myeloid and lymphoid tumors, and provide much needed coverage in transplant biology. A study guide highlights key chapter points, making the text suitable for boards review in hematopathology and hematology-oncology.
to Diagnosis and Laboratory Techniques -- Approaches to Classification of Lymphoma and Leukemia -- Immunohistochemical Profiling of Lymphoma -- Flow Cytometry in the Evaluation of Hematologic Malignancies -- Molecular Diagnostics and Cytogenetic Testing -- Neoplasms of the Bone Marrow -- The Bone Marrow in Normal and Disease States -- Myelodysplastic Syndromes and Myelodysplastic/Myeloproliferative Neoplasms -- Acute Myeloid Leukemia -- Treatment of Acute Myeloid Leukemia and Myelodysplastic Syndromes -- Myeloproliferative Neoplasms -- Chronic Myelogenous Leukemia -- Treatment of Myeloproliferative Neoplasms -- Tumors of the Lymph Node and Extranodal Tissues -- Lymph Node Biology and Lymphadenitis -- Lymphoblastic Leukemia and Lymphoma -- Chronic Lymphocytic Leukemia and Small Lymphocytic Lymphoma -- Marginal Zone Lymphomas -- Follicular Lymphoma and Mantle Cell Lymphoma -- Aggressive B-cell Lymphomas: Diffuse Large B-cell Lymphoma and Burkitt Lymphoma -- Therapy of B-cell Lymphoproliferative Disorders -- Plasma Cell Myeloma and Other Plasma Cell Dyscrasias -- Hodgkin Lymphoma -- Treatment of Hodgkin Lymphoma -- Classification of T-cell and NK-cell Malignancies -- Clinical Management of Non-cutaneous T-cell and NK-cell Malignancies -- Cutaneous T-cell Lymphomas -- Treatment of Cutaneous T-cell Lymphomas -- Histiocytic and Dendritic Cell Neoplasms -- Extranodal Lymphomas and Tumors of the Thymus -- Stem Cell Transplantation -- Clinical Aspects of Hematopoietic Stem Cell Transplantation -- Post-transplant Molecular Monitoring -- Post-transplant Immune Function and the Development of Lymphoma -- Experimental Hematopathology -- Hematopoiesis and Stem Cell Biology -- Role of Host Genetics in Lymphoma -- Developing Prognostic Models for Diffuse Large B-cell Lymphoma -- Growth Signaling and Survival Pathways in Aggressive B-cell Lymphoma -- Proteomic Profiling and Target Identification in Lymphoma -- Mouse Models of Lymphoma and Lymphoid Leukemia -- Mouse Models of Myeloid Leukemia -- Designing Targeted Therapies for Lymphomas and Leukemias.
Keywords: Medicine; Internal medicine; Hematology; Oncology; Pathology; Medicine & Public Health; Pathology; Hematology; Oncology; Internal Medicine